Discussion on the New Trends of International Trade and Its Countermeasures in the Digital Era - Gao, Xiaoyan (International Journal of Global Economics and Management, 2024)
With the advent of the digital economy era, international trade is undergoing profound changes. This study analyzes in detail the new trends and challenges of international trade in the era of digital economy, including the wide application of digital technology, the new characteristics of data flow, and the reconstruction of digital trade rules. On this basis, the corresponding countermeasures and suggestions are put forward, aiming to promote the sustainable development of international trade in the era of digital economy.